Child with epilepsy in school environment - The development of a conceptual model - Brabcová Buršíková, Dana; Kohout, Jiří; Komzáková, Martina; Nohavová, Alena; Tegelová, Vendula (Epilepsy & behavior, 2025)
OBJECTIVE: The aim of this qualitative study is to develop a conceptual model for the school life of the children with epilepsy based on grounded theory methodological framework. METHODOLOGY: A total of 20 children with epilepsy participated in the semi-structured interviews. Inclusion criteria were age of 8-15 years, IQ higher than 70, duration of epilepsy of at least of two years and attendance of mainstream schools. 15 children had never seizure in school and 16 of them have not had a seizure in last 12 months. Qualitative research data was processed based on grounded theory with open coding leading consecutively to several main categories, axial coding establishing connections between individual categories, and finally selective coding resulting in one central category which was the core of the developed conceptual model. RESULTS: Eight main categories were identified during open coding: type of epilepsy and its management, sources of stress at school, adaptive responses to stressors, safe school environment in relation to (a) epilepsy and (b) learning, family support, stability of experience and behavior, and positive self-concept. Axial and selective coding resulted in establishment of Adaptive responses to stressors as the central category which is in the developed conceptual model determined by relevant external and internal factors as well as the sources enabling effective adaptation. CONCLUSIONS: The presented research emphasize the importance of adaptive responses to stressors in the school environment among children with epilepsy which may be useful in counselling focused on how to avoid or successfully manage possible traumatizing experience related with epilepsy in this group.
Keywords: Adaptation, Psychological; Male; Self Concept; Adolescent; Seizure control; Child; psychický stres; sebepojetí; zakotvená teorie; dítě; mužské pohlaví; adaptace psychologická; epilepsie; mladiství; kvalitativní výzkum; Children with epilepsy; Schools; školy; lidé; Grounded Theory; ženské pohlaví; Humans; Stress, Psychological; Adaptive reaction to stressors; Grounded theory; Epilepsy; Qualitative Research; Female; Type of epilepsy; School environment; Conceptual model